Nanotechnological Applications in Food Packaging, Sensors and Bioactive Delivery Systems - Das Purkayastha, Manashi; Manhar, Ajay Kumar (Nanoscience in Food and Agriculture 2, 2016)
The development of nanomaterial-based products has boosted research in food science. Packaging has been the core subject of research in food nanotechnology. The mechanical and barrier performance of packaging are improved by nanocomposites. Intelligent packaging with communication functions is currently being developed using indicators of oxygen, humidity and freshness. However the concern of nanoparticle migration into the food must be addressed prior to commercial use. For biosensors, functionalized nanomaterials act as catalytic or immobilization platform or as electro-optical labels for enhancing the sensitivity and selectivity of the detection. Other functions of nanomaterials include encapsulation, protection, and enhancement of the solubility and bioavailability of active food ingredients. This review describes nanocomposites as high barrier packaging material, nano-sensors to achieve safer foods with lower incidence of chemical contaminants or adulterants or pathogenic microorganisms, and nanoencapsulation strategies as innovative delivery systems of bioactive compounds. The technical aspects of these topics are discussed with respect to synthesis, mode of action and functional performance.